Controle biológico de Dolops carvalhoi (Crustacea: Branchiura) em juvenis de pacu (Piaractus mesopotamicus) - Genovez, Lara Wichr; Pilarski, Fabiana [UNESP]; Sakabe, Roberson; do Amaral Marques, Mauricio Pires; de Moraes, Flavio Ruas [UNESP] (Inst Pesca, 2008)
This work evaluated piaucu juveniles (Leporinus macrocephalus) efficiency on the control of Dolops carvalhoi in pacu (Piaractus mesopotamicus) under artificial infestation. 30 fish were equally distributed in six aquarium and acclimated for seven days. After this period the pacus were unnaturaly infested with 20 D. carvalhoi per fish to four days. on the fifth day, for aquaria were added with five uninfected piaucus each and the fish were checked eight times to evaluted the total number of parasites in fish body and aquarium wall. After 24 hours in the aquarium with piaucus the total number of Dolops was significant lower than only pacus suggesting that piaucu preyed the parasite. The parasite number was reduced 15 minutes after the addition of piaucus and after 24 hours, no parasites was found in pacu body and aquarium walls, suggesting that piaucu fingerling may be used to branchiurans infestations in other species of fish.
Biological control of Dolops Carvalhoi (Crustacea: Branchiura) in pacu juveniles (Piaractus mesopotamicus)
Keywords: Dolops carvalhoi; Leporinus macrocephalus; Piaractus mesopotamicus; Biological control